Desentralisasi dan Penyediaan Layanan Publik di Negara-Negara Demokrasi yang masih Berkembang - Sumardi Sumardi; Nasir Nasir; Kahar Gani; Abdul Halim; Nasiratunnisa Mallappiang (Indonesian Journal Publisher, 2025)
This study examines the relationship between decentralization and the provision of public services in developing democratic countries. Decentralization is often considered a governance reform strategy aimed at improving efficiency, responsiveness, and the quality of public services by granting greater authority to local governments. However, the implementation of decentralization in many developing countries has produced varied outcomes, particularly in relation to local government institutional capacity, levels of accountability and transparency, and public participation in service delivery processes. This study aims to analyze how decentralization influences the quality of public service provision in developing democratic states. The research employs a qualitative approach through a systematic literature analysis using NVivo software to identify patterns, themes, and relationships among concepts across previous studies. The findings indicate that decentralization can enhance the quality of public services when supported by adequate local government capacity, transparent and accountable governance systems, and active public participation in decision-making and policy oversight. Conversely, limited institutional capacity and weak oversight mechanisms may lead to disparities in service quality across regions. The study concludes that the success of decentralization in improving public service delivery largely depends on the strength of local governance institutions and the broader democratic governance framework that supports them.